Faktor-Faktor yang Mempengaruhi Kecemasan Mahasiswa dalam Menghadapi Praktik Klinik Keperawatan - Ramadhan Trybahari Sugiharno; Wibowo Hanafi Ari Susanto; Ardiansa Ardiansa; Frengki Wospakrik; Ester Ester (Jurnal Keperawatan Silampari, 2022)
This study aims to look at the factors that influence student anxiety in facing clinical nursing practice. This research is a quantitative study using a cross-sectional study design approach. The results showed that the majority of respondents (69.14%) were female, 56 people, and most of the 39 respondents (48.1%) of all respondents had moderate anxiety. In addition, 51 respondents (63%) had good knowledge, up to 52 respondents (64.2%) had good skills, 61 respondents (75.3%) had significant supervisory influence, and 46 respondents (56.8% ) had an excellent environmental effect. In conclusion, there is an important relationship between knowledge, skills, supervisors, and the environment with students' anxiety in facing clinical nursing practice. Keywords: Anxiety, Nursing, Students, Clinical Practice